2013
DOI: 10.1111/nyas.12067
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal evidence for variable patterns of handedness in chimpanzees, human hunter–gatherers, and recent British populations

Abstract: Previous studies have shown a strong correspondence between long bone bilateral asymmetry and reported handedness. Here, we compare the pattern of asymmetry in mechanical properties of the humerus and second metacarpal of Pan troglodytes, recent British industrial and medieval populations, and a broad range of human hunter-gatherers, to test whether technological variation corresponds with lateralization in bone function. The results suggest that P. troglodytes are left-lateralized in the morphology of the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 109 publications
(277 reference statements)
4
21
0
Order By: Relevance
“…Our findings complement previous studies about shaft cross-section (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013). These authors concluded that the diaphysis is the most asymmetric region in the humerus in response to physical activity, because in the shaft higher mechanical stresses provoke greater muscle pressures in the bone, causing an increase in cortical bone (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013). Therefore physical activity causes an increase in the thickness of the cortical bone in the diaphysis, but the shape of the shaft can be explained by size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings complement previous studies about shaft cross-section (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013). These authors concluded that the diaphysis is the most asymmetric region in the humerus in response to physical activity, because in the shaft higher mechanical stresses provoke greater muscle pressures in the bone, causing an increase in cortical bone (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013). Therefore physical activity causes an increase in the thickness of the cortical bone in the diaphysis, but the shape of the shaft can be explained by size.…”
Section: Discussionsupporting
confidence: 92%
“…These results show that the relative length of the muscle attachments depends on shaft size: when the shaft is greater, the muscle attachment will be longer. Our findings complement previous studies about shaft cross-section (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013). These authors concluded that the diaphysis is the most asymmetric region in the humerus in response to physical activity, because in the shaft higher mechanical stresses provoke greater muscle pressures in the bone, causing an increase in cortical bone (Cuk et al, 2001;Auerbach and Ruff, 2006;Stock et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Percent directional asymmetry provides a measure of both the magnitude of asymmetry and its direction: positive %DA indicates relative hypertrophy in the right humerus compared to the left, and vice versa when %DA is negative. Following Stock and colleagues [107], a 0% cut-off was used to determine right-bias frequencies for TA and J ; Auerbach and Ruff [30] showed that similar results were found when 0%, 0.5%, or 1% DA was used as a cut-off distinguishing handedness from fluctuating asymmetry. However, three individuals with very low asymmetry (one Iron Age Brno-Maloměřice male, and two Bronze Age females from Ostojićevo and Brno-Tuřany) were slightly negative in one property but slightly positive in the other, resulting in different percentages of right-bias for TA and J .…”
Section: Methodsmentioning
confidence: 97%
“…Skeletal robusticity, or relative bone strength, is largely responsive to patterns of habitual activity during life, leading to a correlation between bone morphology and patterns of activity (Ruff, 2008). The underlying biological mechanism for bone functional adaptation is complex (Pearson and Lieberman, 2004), however there is significant evidence that mechanical loading influences the distribution of cortical bone in long bone diaphyses (Robling et al, 2000;Ruff et al, 2006;Stock, 2009a, 2009b;Stock et al, 2013). The most commonly used method of analysis of long bone robusticity uses engineering formulae for hollow beams to estimate the mechanical performance of bones based on the distribution of cortical bone in diaphyseal cross-sections to calculate strength properties which are standardized to body mass prior to comparison (Larsen, 1997;Ruff, 2000).…”
Section: Skeletal Biomechanicsmentioning
confidence: 96%